Comparative Evaluation of Poly Aluminum Chloride (PAC) and Aluminum Chlorohydrate (ACH) in Pre Treatment of Boiler Feed Water - Antika, Fitria Mega; Saputra, Asep Handaya (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2025)
Industrial boiler feed water from rivers and groundwater requires treatment to remove impurities causing scaling and corrosion. In this study, water treatment was carried out using the coagulationflocculation method with Poly Aluminum Chloride (PAC) and Aluminum Chlorohydrate (ACH) as coagulants, with the aim of comparing their performance and cost-effectiveness. Jar tests were performed with coagulant dosages of 40, 60, and 80 ppm and rapid mixing speeds of 90, 120, and 150 rpm. Metal reduction experiments were conducted by adding Fe and Cu at concentrations of 1, 3, and 5 ppm. The results showed that the optimum dosages for turbidity and metal removal were 80 ppm for PAC and 40 ppm for ACH, while the optimum dosages for COD reduction were 60 ppm for PAC and 40 ppm for ACH. Rapid mixing at 90 rpm was most effective for turbidity reduction, whereas 120 rpm was optimal for metal and COD removal. Overall, ACH was found to be more effective and more cost-efficient than PAC for the pretreatment of boiler feed water